Effective Model of Knowledge-Based Transformation and Sustainable Development in BRICS-T Countries - Pessoa, G.; Orynbassarova, Ye.; Sabyrzhan, A.; Renobell, V.; Ponkratov, V.; Kaldibayev, N.; Nikolaeva, I.; Pozdnyaev, A.; Shkalenko, A.; Philippov, D.; Dudnik, O. (Emerging Science Journal, 2025)
This article presents a novel empirical framework for evaluating knowledge-based transformation and sustainable development in BRICS-T countries. The framework is based on an integrated Triple Helix assessment model that quantifies the interrelationships between research output, educational innovation, industry engagement, market alignment and policy support. Using a comprehensive dataset from 60 universities across BRICS-T countries, combined with an AHP-based weighting system derived from 24 cross-sector experts, this study reveals previously unidentified patterns in innovation and educational outcomes. Our method demonstrates that only research output (β = 0.375, p < 0.001) and industry engagement (β = 0.418, p < 0.001) consistently predict innovation output across all BRICS-T countries, while market alignment influences educational quality in only four out of the six nations. The analytical framework successfully quantifies significant performance variations across countries, with innovation output scores ranging from 2.89 to 4.23 and educational quality scores ranging from 3.08 to 4.15. The findings contribute to Triple Helix theory through country-specific decomposition of relationships, supplementing existing knowledge-based economy theories with quantitative evidence of differential effectiveness across emerging economies. This methodology can be implemented for strategic planning in higher education systems transitioning from resource-based to knowledge-based economies.
Keywords: Triple Helix Model; BRICS-T Countries; Innovation Output; Educational Quality; University-Industry Collaboration; Knowledge-based Economy; Research Output; Cross-Country Analysis; Resource-based Economy; Development Challenges